The century of taste : the philosophical odyssey of taste in the eighteenth century - Dickie, George, 1926- (Oxford University Press, 1996)
The Century of Taste offers an exposition and critical account of the central figures in the early development of the modern philosophy of art. Dickie traces the modern theory of taste from its first formulation by Francis Hutcheson, to blind alleys followed by Alexander Gerard and Archibald Allison, its refinement and complete expression by Hume, and finally to its decline in the hands of Kant. In a clear and straightforward style, Dickie offers sympathetic discussions of the theoretical aims of these philosophers, but does not shy from controversy--pointing out, for instance, the obscurities.